Arthropod Population in The Canopy of Cucumber (Cucumis sativus L.) Plants in Talang Ilir Hamlet, Banyuasin Regency - Haperidah Nunilahwati; Laili Nisfuriah; Yani Purwanti; Dali Dali; Marlina Marlina; Khodijah Khodijah; Oktha Vianto (Universitas Muhammadiyah Palembang, 2023)
Arthropods are a diverse group of animals and play an important role in agricultural ecosystems, including in cucumber plantings in Talang Ilir Hamlet, Banyuasin Regency. This research aims to determine the diversity and abundance of arthropods in the canopy of cucumber plantations in Talang Ilir Hamlet, Banyuasin Regency. The research was carried out in February and April 2023 at 3 cucumber planting locations in Talang Ilir Hamlet, Banyuasin Regency. Observations were made by identifying, and recording the number and type of arthropods at different times in each location. The research used a Factorial Randomized Block Design and the research data were analyzed using analysis of variance (ANOVA) and a further BNT test at 5% level. The research results showed that the arthropod species found at the 3 observation locations were Coccinella sp, Aulacophora sp, Diaphania sp, Spodoptera sp, Ideopsis sp, and Apis sp. The highest average number of arthropods was found in A2 (Diaphania sp) 3.37 individuals, and followed by A5 (Apis sp), A1 (Coccinella sp), A6 (Ideopsis sp), A3 (Aulacophora sp) and A4 (Spodoptera sp) respectively. 2.90, 1.77, 1.47, 1.23 and 0.10 tails. Location 1 (L1) had a higher average number of arthropods, namely 2.22 compared to Location 2 (L2) 1.57 and Location 3 (L3) 1.63 arthropods. Based on the type and location of observations, it was concluded that there were significant differences in the number of arthropods in the cucumber plantings of Talang Ilir Hamlet, Banyuasin Regency.